2021
DOI: 10.1167/tvst.10.9.12
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Scattering, Blinking Rate, and Tear Film Osmolarity After Exposure to Environmental Stress

Abstract: Dry environments, such as those in offices or aircraft cabins, can potentially generate ocular discomfort and alter the tear film. We compare light scatter, blinking rate, and tear osmolarity in young and older subjects after exposure to low humidity using a controlled environmental chamber.Methods: Two groups of healthy subjects were recruited; younger (N = 13, 27 ± 6 years) and older (N = 23, 71 ± 7 years). Measurements were carried out before and after 90minute exposure to low relative humidity (5%) and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 59 publications
(69 reference statements)
1
5
0
Order By: Relevance
“…A significant increase in the blinking rate was observed after exposure to low humidity, showing, on average, three more blinks per minute compared with before the exposure ( p = 0.01), in line with previous work 40 . However, in comparison, the magnitude of the blinking rate increase was relatively small compared to the nearly doubling of the blink ratio that occurred when comparing CL with spectacle wear (see previous subsection).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A significant increase in the blinking rate was observed after exposure to low humidity, showing, on average, three more blinks per minute compared with before the exposure ( p = 0.01), in line with previous work 40 . However, in comparison, the magnitude of the blinking rate increase was relatively small compared to the nearly doubling of the blink ratio that occurred when comparing CL with spectacle wear (see previous subsection).…”
Section: Discussionsupporting
confidence: 89%
“…A significant increase in the blinking rate was observed after exposure to low humidity, showing, on average, three more blinks per minute compared with before the exposure (p = 0.01), in line with previous work. 40 However, in comparison, the magnitude of the blinking rate increase was relatively small compared to the nearly doubling of the blink ratio that occurred when comparing CL with spectacle wear (see previous subsection). This suggests that the tear film thinning, other tear disturbances and changes on the ocular surface generated by inserting a CL onto the eye have a much larger effect than occurring after 1.5 h of exposure to low humidity.…”
Section: Exposure To Low Humidity On the Ocular Surfacementioning
confidence: 83%
“…In support of our findings, a recent study indicated that exposure to low relative humidity on tear film adversely affected the rate of evaporation, the thickness, and stability of the lipid layer, and the production of tears; this resulted in significant postoperative discomfort. A dry environment increases light scattering, especially in older adults, who need to blink more frequently to prevent their corneas from becoming dehydrated ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…The MTF is the ratio of the contrast of the image to the object in terms of the frequency of an object [17]. .The SR indicates a perfect optical system at a value of 1 [18]. Hence, higher MTF and SR values usually indicate better objective optical quality [19,20].…”
Section: Objective Optical Quality Assessmentmentioning
confidence: 99%